Literasi Kesehatan Mental Orang Dewasa dan Penggunaan Pelayanan Kesehatan Mental - Handayani, Trisni; Ayubi, Dian; Anshari, Dien (UI Scholars Hub, 2020)
Background. In Indonesia, prevalence of emotional mental disorder has increased from 6% in 2013 to 9.8% in 2018. Mental health service has not optimally utilized by people with mental health problems in East Bogor sub-district. Objective. This study aimed to determine the relationship of mental health literacy with mental health service use. Method. This study used a cross sectional design with a quantitative approach. Respondents were people with mental health problems who lived in East Bogor Sub-District. A total of 139 respondents were selected using multistage random sampling technique. Data were collected by in-person interview using a questionnaire. Data were analysed using a multiple logistic regression test for multivariate model selection. Results. The results of this study showed that the mean score of mental health literacy was 73.08 (scale of 100). There were 56.1% respondents utilized mental health services. As many as 57.6% respondents aged ≥30 years. Among those who have high mental health literacy, 64.9% of them have utilized mental health services. Results from multivariate analysis showed that there was a significant relationship between mental health literacy and the use of mental health service in people with mental health problems, after adjustment with gender and mental health service availability. Conclusion. People with high mental health literacy tended to use mental health services compared to those with low literacy.